Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV METEOR during cruise M73/1 - Frank Strozyk; Jan F Metzen; Sebastian Krastel; Volkhard Spieß; Achim J Kopf (PANGAEA, 2025)
Raw multibeam bathymetry data were collected using the ship extquotesingles own SIMRAD EM710 multibeam echosounder during the RV METEOR cruise M73/1 WestMed. The cruise took place between 2007-07-21 and 2007-08-12 (Cadiz, Spain – Genoa, Italy). During leg M73/1, EM710 data were collected in the EEZ of France between 2007-07-25 and 2007-08-06. These data are of worse quality than the EM120 multibeam bathymetry data collected on the same cruise, and might have been acquired in a test mode. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus no SVP files are added to this dataset. Data are unprocessed and therefore contain incorrect depth measurements (artifacts). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).